Framing policy coherence toward improving climate-adaptive water productivity in Egypt - Eldabbagh, Fayrouz; Abdelwahab, Noura; Brouziyne, Youssef; Sanchez Ramirez, Juan Carlos; Nicol, Alan (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2024)
The interconnectedness between food, land, and water resources is evident where the use of one resource could generate externalities for others. The uncertainties around global markets challenge economies in the global south and climate change further exacerbates the urgent need for integrated management of natural resources and optimized investments and interventions. Moreover, the interconnections of natural resources and the biophysical environment influence the livelihoods and income of land and water users. Therefore, the partial or complete absence of coherence between sectoral public policies and inter-institutional linkages hampers the ability to address key interdependencies between food, land, and water resources and the three pillars of sustainable development: environment, economy, and society. The study offers an analysis of coherent water productivity policies between the different relevant strategies in Egypt towards a potential coordinated and integrated policy environment contributing to water and food security and sustainable development. Accordingly, it presents the synergies and trade-offs between policy objectives and instruments and the existing stakeholders' cross-coordination mechanisms, which are significant for enhancing policy coherence.